2020
DOI: 10.3389/fpsyg.2020.01236
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Self-Assessed State of Health and Vitamin D Knowledge in Emirati and International Female Students in United Arab Emirates (UAE)

Abstract: Introduction: Globally, vitamin D deficiency is one of the most common deficiencies, affecting nearly half the world's population. The objective of this survey was to assess and compare the knowledge about vitamin D and the perceived state of health in Emirati and international tourist female students in Dubai, United Arab Emirates (UAE). Methods: This is a cross-sectional study that took place in universities in Dubai, United Arab Emirates. This survey consisted of 17 multiple choice questions and was adapted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
1
4
1
Order By: Relevance
“…Many answered incorrectly regarding factors that impacted vitamin D synthesis such as latitude, season, time of day, sunscreen application, and skin pigmentation. Inaccurate nutrition knowledge was re-markable regarding red meat as only 13% indicated the right answer about red meat as a source of Vitamin D. In line with our study, several quantitative and qualitative studies at the international, national, and local levels showed a lack of knowledge about vitamin D dietary sources, health benefits, complications related to vitamin D deficiency, and updated vitamin D recommendations [20,32,33,37,[39][40][41]. This points to the need for better targeted educational interventions.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Many answered incorrectly regarding factors that impacted vitamin D synthesis such as latitude, season, time of day, sunscreen application, and skin pigmentation. Inaccurate nutrition knowledge was re-markable regarding red meat as only 13% indicated the right answer about red meat as a source of Vitamin D. In line with our study, several quantitative and qualitative studies at the international, national, and local levels showed a lack of knowledge about vitamin D dietary sources, health benefits, complications related to vitamin D deficiency, and updated vitamin D recommendations [20,32,33,37,[39][40][41]. This points to the need for better targeted educational interventions.…”
Section: Discussionsupporting
confidence: 84%
“…Those who reported previous testing for their vitamin D levels accounted for 77% of the total participants. This is unlike other studies conducted in the UAE that found vitamin D testing to be uncommon among their participants [15,22,37]. Moreover, 77% of participants were taking supplements.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…In a recent investigation among young student (aged 18–25 years) in Pakistan, only 9% of individuals were able to identify the correct food sources of Vit D, 33% were aware of the bone health advantages of Vit D and 36% knew that sunlight exposure was a major factor affecting Vit D synthesis in body [ 40 ]. Also, knowledge about Vit D, its sources and health benefits was very limited (28.8%) in Emirati and International tourist students in Dubai [ 41 ].…”
Section: Discussionmentioning
confidence: 99%